Legal Protection of Pets from Threats of Violent Criminal Acts and Neglect by their Owners - Susanti, Christine; Sukardi, Ellora; Pasaribu, Debora (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
Indonesia is one of the countries in the world with the most cases of animal violence. The violence ironically also occurs in pets that should receive protection and good care by their owners. In addition to violence, pets are even abandoned by their owners, while it is known that the Indonesian ius constitutum requires animal owners, including pets, to take good care of their animals until they die naturally. This study wants to examine how Indonesian law regulates obligations for animal owners towards their pets, legal protection of pets from acts of violence and neglect committed by owners, and to prevent similar acts from being repeated because apart from these acts violate the applicable legal rules, not in accordance with the dignity and dignity of the Indonesian nation as a civilized nation, it also has the potential to cause an impact/disturbance to order, peace, and public health and the surrounding environment. The research method used is normative juridical with the nature of qualitative analysis using primary legal materials, namely Law Number 41 of 2014 concerning Livestock and Animal Health, Government Regulation Number 95 of 2012 concerning Veterinary Public Health and Animal Welfare and the Criminal Code (KUHP); secondary legal materials; and tertiary legal materials. The results of this study state that acts of violence and abandonment of pets by owners are included in the category of criminal acts, namely crimes and perpetrators can be subject to criminal sanctions.